BNIP3L-mediated mitophagy is required for mitochondrial remodeling during the differentiation of optic nerve oligodendrocytes. Issue 10 (3rd October 2021) - Yazdankhah, Meysam; Ghosh, Sayan; Shang, Peng; Stepicheva, Nadezda; Hose, Stacey; Liu, Haitao; Chamling, Xitiz; Tian, Shenghe; Sullivan, Mara L.G.; Calderon, Michael Joseph; Fitting, Christopher S.; Weiss, Joseph; et al.
ABSTRACT: Retinal ganglion cell axons are heavily myelinated (98%) and myelin damage in the optic nerve (ON) severely affects vision. Understanding the molecular mechanism of oligodendrocyte progenitor cell (OPC) differentiation into mature oligodendrocytes will be essential for developing new therapeutic approaches for ON demyelinating diseases. To this end, we developed a new method for isolation and culture of ON-derived oligodendrocyte lineage cells and used it to study OPC differentiation. A critical aspect of cellular differentiation is macroautophagy/autophagy, a catabolic process that allows for cell remodeling by degradation of excess or damaged cellular molecules and organelles. Knockdown of ATG9A and BECN1 (pro-autophagic proteins involved in the early stages of autophagosome formation) led to a significant reduction in proliferation and survival of OPCs. We also found that autophagy flux (a measure of autophagic degradation activity) is significantly increased during progression of oligodendrocyte differentiation. Additionally, we demonstrate a significant change in mitochondrial dynamics during oligodendrocyte differentiation, which is associated with a significant increase in programmed mitophagy (selective autophagic clearance of mitochondria). This process is mediated by the mitophagy receptor BNIP3L (BCL2/adenovirus E1B interacting protein 3-like). BNIP3L-mediated mitophagy plays a crucial role in the regulation of mitochondrial network formation, mitochondrial function and the viability of newly differentiated oligodendrocytes. Our studies provide novel evidence that proper mitochondrial dynamics is required for establishment of functional mitochondria in mature oligodendrocytes. These findings are significant because targeting BNIP3L-mediated programmed mitophagy may provide a novel therapeutic approach for stimulating myelin repair in ON demyelinating diseases. Abbreviations: A2B5: a surface antigen of oligodendrocytes precursor cells, A2B5 clone 105; ACTB: actin, beta; APC: an antibody to label mature oligodendrocytes, anti-adenomatous polyposis coli clone CC1; ATG5: autophagy related 5; ATG7: autophagy related 7; ATG9A: autophagy related 9A; AU: arbitrary units; BafA1: bafilomycin A1; BCL2: B cell leukemia/lymphoma 2; BECN1: beclin 1, autophagy related; BNIP3: BCL2/adenovirus E1B interacting protein 3; BNIP3L/NIX: BCL2/adenovirus E1B interacting protein 3-like; CASP3: caspase 3; CNP: 2′, 3′-cyclic nucleotide 3′-phosphodiesterase; Ctl: control; COX8: cytochrome c oxidase subunit; CSPG4/NG2: chondroitin sulfate proteoglycan 4; DAPI: 4′6-diamino-2-phenylindole; DNM1L: dynamin 1-like; EGFP: enhanced green fluorescent protein; FACS: fluorescence-activated cell sorting; FIS1: fission, mitochondrial 1; FUNDC1: FUN14 domain containing 1; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFAP: glial fibrillary growth factor; GFP: green fluorescent protein; HsESC: human embryonic stem cell; IEM: immunoelectron microscopy; LAMP1: lysosomal-associated membrane protein 1; LC3B: microtubule-associated protein 1 light chain 3; MBP: myelin basic protein; MFN2: mitofusin 2; Mito-Keima: mitochondria-targeted monomeric keima-red; Mito-GFP: mitochondria-green fluorescent protein; Mito-RFP: mitochondria-red fluorescent protein; MitoSOX: red mitochondrial superoxide probe; MKI67: antigen identified by monoclonal antibody Ki 67; MMP: mitochondrial membrane potential; O4: oligodendrocyte marker O4; OLIG2: oligodendrocyte transcription factor 2; ON: optic nerve; OPA1: OPA1, mitochondrial dynamin like GTPase; OPC: oligodendrocyte progenitor cell; PDL: poly-D-lysine; PINK1: PTEN induced putative kinase 1; PRKN/Parkin: parkin RBR E3 ubiquitin protein ligase; RFP: red fluorescent protein; RGC: retinal ganglion cell; ROS: reactive oxygen species; RT-PCR: real time polymerase chain reaction; SEM: standard error of the mean; SOD2: superoxide dismutase 2, mitochondrial; SQSTM1/p62: sequestosome 1; TEM: transmission electron microscopy; TMRM: tetramethylrhodamine methyl ester; TOMM20: translocase of outer mitochondrial membrane 20; TUBB: tubulin, beta; TUBB3: tubulin, beta 3 class III.